Society 5.0: Shaping the future of e-commerce - Arturs Bernovskis; Deniss Sceulovs; Agnis Stibe (Journal of Open Innovation: Technology, Market and Complexity)
This paper explores the impact of Society 5.0, a Japanese initiative that integrates digital and physical spaces to address societal challenges and drive economic growth. It examines the role of decentralized technologies in enhancing e-commerce by adapting to consumer behavior changes and improving market dynamics. The study details the transition from Web 1.0’s basic functionalities to the more interactive and social Web 2.0, setting the stage for a more integrated and intelligent e-commerce environment under Society 5.0. This new paradigm emphasizes personalized consumer experiences facilitated by AI and big data, focusing on real-time data, predictive analytics, and tailored services. The paper also addresses how Society 5.0 prioritizes sustainability and ethical practices in AI, aligning e-commerce strategies with global sustainability goals through eco-friendly practices and green logistics. The methodology involves a detailed literature review using specified databases over a defined period, applying rigorous criteria for article selection and classification to ensure comprehensive topic coverage. This research highlights the potential of cutting-edge technologies to revolutionize e-commerce by making it more secure, efficient, and aligned with consumer expectations and environmental standards. The research employs a qualitative approach, synthesizing existing literature on Society 5.0 and its potential impact on e-commerce. We explore how blockchain and big data will personalize experiences, enhance operational efficiency, and introduce new products and services. While acknowledging the limitations of relying solely on secondary literature, the paper underscores the need for future research to include empirical studies and address challenges like data privacy, the digital divide, and evolving regulatory frameworks within the e-commerce landscape.